A bridge between the protection of future generations and the preservation of human remains in museums - Ciliberti, Rosagemma (Medicina Historica, 2023)
Unesco's approach to safeguarding future generations through the Universal Declaration of Bioethics and Human Rights provides a significant framework for examining the preservation of human remains in museums. Understanding this practice in the light of ethics, science and culture is essential to ensure that future generations can learn from the past without compromising respect for the deceased and their traditions. Through balanced reflection and active engagement of stakeholder, a respectful and informative approach to the preservation of human remains in museums can be created for a future enriched by knowledge and understanding of the past. Through a multidisciplinary approach that involves experts in bioethics, anthropology, history, and cultural studies, museums can develop comprehensive policies for the respectful curation and display of human remains.